THE CHARACTERISTIC VARIATION OF T_b IN THE ANTARCTIC REGION REVEALED BY NOAA AVHRR CHANNEL-4 DATA - セコ, カツモト; ワダ, マコト; アオキ, シュンジ; SEKO, Katsumoto; WADA, Makoto; AOKI, Shuhji (National Institute of Polar Research, 1991)
P(論文) Based on the daily variation of T_b of NOAA AVHRR channel-4 data, several characteristic features of the variation of T_b in the Antarctic region were presented. Remarkable differences in the T_b variation between ocean and continent were found. The amplitude of the seasonal cycle of the T_b variation is much larger over the continent than the ocean, because of the strong inversion over the continent in winter. The short term T_b variation within 10 days over the ocean is controlled by synoptic disturbances. The T_b variation over the continent revealed longer periodicity of a few tens of days. The variation is caused by the cloud intrusion into the Antarctic continent. departmental bulletin paper